Performance of dairy cows in pasture supplemented with levels of concentrate and crude protein - Oliveira, Aline Guimarães de; Oliveira, Veronaldo Souza de; Santos, Gladston Rafael de Arruda; Santos, Anselmo Domingos Ferreira; Sobrinho, Diomar Claudio dos Santos; Oliveira, Fábio Luiz de; Santana, José Augusto; Goveia, Julianne Santiago Silva (Semina: Ciências Agrárias, 2014)
The objective of this study was to evaluate the effect of four levels of concentrate (0, 1, 3 and 5 kg/ cow/day) and two of crude protein (CP) (14 and 18% crude protein in dry matter of concentrate) on performance (milk production and composition), intake and apparent nutrient digestibility, and plasma urea nitrogen concentration (PUN) of lactating cows in rotational Tanzânia (Panicum maximum Jacq. cv. Tanzânia) pasture. Eight crossbred cows (Holstein-Gir) with average weight of 488 kg and average production of 12 kg of milk/cow/day, were used. The experimental design was a latin square (4x4), with four animals and four experimental diets, being used two latin squares simultaneously and individualized, each one with a CP level. Were observed influences of CP levels on CP, non-fiber carbohydrates (NFC) and total carbohydrates (TC) intakes. Dry matter (DM), crude protein, ether extract (EE), CNF, CT and total digestible nutrients (TDN) intakes increased as the concentrates were provided both as 14% (C14) to 18% CP (C18), individually. Neutral detergent fiber (NDF) intake decreased as the concentrates were provided. The CP levels did not influence the apparent digestibility of DM, CP, NDF, EE and CT. However, there was an increase in the DM apparent digestibility of groups C14 and C18 individually. No influence were observed of concentrate levels and CP on PUN, milk production and composition. The results show that the rotational grazing of Tanzania, without supplementation, is the best option for milk production during the rainy season for crossbred cows with an average production of 12 kg milk/cow/day.